Gamification in hidden education-teaching migration-related topics through the didactic board game "crossing borders" - Mojca ILC KLUN (European Journal of Geography)
Slovenia, one of the smallest European countries, has always been part of various migration processes. As these processes are nowadays an important part of politics and our everyday life, the topics of migration need to be included in the school curricula. The paper presents an example of how educators can teach young people about migration processes through gamification, using an innovative, didactic and strategic board game Crossing Borders. When playing Crossing Borders, players subconsciously learn about the migration-related topics. The game was very well received among all test groups (teachers and students).